Pemberdayaan Sumber Daya Air untuk Berbagai Kepentingan Secara Berkelanjutan - Sangkawati, Sri; Hadihardaja, Joetata (MEDIA KOMUNIKASI TEKNIK SIPIL, 2005)
Water is essential for human life, for agricultural, industrial production and for water-based recreation and transportation. It is central to many national concern, including energy, food production, environmental quality, and regional economic development. Water as a public comodity which is not have valuable value, this condition will encourage the over consumpsion of the water. In the future, the management of water resources in Indonesia will be more difficult. The water demand will be increased as result population growth, in other hand the water resources will be more rare. The limitation of water supply will be a cause of conflict among community. In accordance of the water resource utilization, which is more and more limited, the water resources should be optimize and integrated and sustained. Privatitation of water resources is not againt the UUD 1945. As long as, the water that will be offer to other community as a result of water surplus of an area. Beside that, it should be improve the welfare of the community Keywords: Sumberdaya air, pengelolaan, pemberdayaan berkelanjutanPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3927[How to cite: Sangkawati, S. dan Hadihardaja, J., 2005, Pemberdayaan Sumber Daya Air untuk Berbagai Kepentingan Secara Berkelanjutan, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 3, pp. 117-127]